MARKETING POLITIK PASANGAN SYAMSUAR – EDY NATAR PADA PEMILIHAN GUBERNUR RIAU PERIODE 2019 – 2024 DI KOTA PEKANBARU TAHUN 2018 - Almer Denish Agrippino; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
In 2018 several regions in Indonesia will hold simultaneous local elections. One of them is Riau Province which is implementing the Simultaneous Local Election followed by several pairs of candidates from Political Parties. One of them is Syamsuar-Edy Natar who is promoted by PAN, PKS, and Nasdem Party and where the pair is able to defeat another candidate pair in the Capital of Riau Province, Pekanbaru City. The couple's success is the result of the political marketing of the couple in Pekanbaru City.The theoretical concept used according to Firmanzah is Marketing Mix which includes 4P (Product, Promotion, Price, and Place). This research was conducted in Pekanbaru City by using descriptive qualitative methods, collecting data through observation and interviews with informants concerned with the research.The results showed that Syamsuar-Edy Natar had segmented targeted voters as a political target in the city of Pekanbaru divided into four groups, namely (1) rational voter groups whose political choices were influenced by performance, vision-mission and work programs as well as the competency or personal qualities of the candidates ; (2) sociological voter groups whose political choices are influenced by religion, regional origin and candidate ethnicity; (3) psychological voter groups whose political choices are influenced by the candidate's personal character, gender and age of the candidate; and (4) floating voter groups which are beginner voters and millennial groups. Syamsuar-Edy Natar's political position in gaining the sympathy of the people of Pekanbaru city is influenced by personal branding in the form of achievement traces achieved by Syamsuar-Edy Natar before, personal character as a person who is religious, religious, honest and intelligent. In addition, Syamsuar-Edy Natar's political positioning is also influenced by the political products that he offers directly in the campaign as well as through political promotion and information dissemination, where the political product is in accordance with what is needed by the people of Pekanbaru. The bearer party, emotional closeness, ethics and the ability to build political communication Keywords:Political Marketing, Local Election, Marketing Mix.